Consolidação da Unioeste: contribuições do movimento estudantil (1990-2015). - Lutz, Amanda Cristina (2023)
This research aims to discuss the importance of the Student Movement (ME) in the consolidation of UNIOESTE during the years 1990 to 2015, a period in which the university sought to become an institution of higher education. The research is justified by the gap on the subject, due to the absence of studies based on the temporal and geographic cutout listed. The research still has a personal justification, as we took part in demonstrations as a Pedagogy student at this same institution during the years 2014 to 2017, in favor of the University Restaurant, a struggle that lasted for about twenty years until its realization. At the regional level, at the beginning of the afore mentioned period, UNIOESTE was going through the recognition process, when academics demonstrated the importance of claims for this process to be consummated. Intending to answer how the historical process of the student manifestations of the academics took place, we used bibliographic and documentary sources about the ME in newspapers, magazines, photos, meeting minutes, COU minutes, research in archives such as: Municipal Public Library of Cascavel / PR , UNIOESTE Campus Cascavel Library, Museum of Image and Sound-Cascavel/PR, private archives, reports from former members of the ME and information collected on social networks and online portals of the DCEs of the five campuses of the university. We discussed the process of stateization and recognition of this institution and the role of students in this space. We identified and addressed the main guidelines claimed by the academics and how they carried out the manifestations in defense of a quality public education and in favor of student assistance that covered all students within this university.